Tanggung Jawab Perusahaan Ekspedisi Atas Kerusakan Dalam Pengiriman Barang (Studi Kasus Shopee Express) - Silfiyana Salsabillah; Hardian Iskandar (LPPM Universitas Ekasakti Padang, 2023)
In the era of electronic commerce that continues to grow, Shopee Express as one of the main players in the e-commerce industry offers efficient and fast delivery services. However, in the process of shipping goods, the risk of damage or loss is always there. This negligence is the responsibility of the expedition company, because the company has an obligation to compensate for losses experienced by consumers. These provisions are contained in Law No. 8 of 1999 concerning Consumer Protection. This research aims to analyze and determine the form of consumer protection against damage to goods in terms of business actors, the role of government up to the settlement stage. The main problem raised in this research is how to protect consumers, especially in the event of damage during the goods delivery process. The research method used in writing this article is normative legal research, data collection techniques by examining library materials or secondary data based on research results that to submit a product replacement claim, consumers are required to submit evidence in the form of photos/videos, provisions that have been made by Shopee Express and approved by the consumer when they want to make a transaction is an absolute decision and cannot be contested.